INTERPRETER TRAINING: TAKING ACCOUNT OF INTERCULTURAL COMMUNICATION (Journal of Contemporary Philology, 2018)
Communication settings involving interpreters are always instances influenced by intercultural factors, due to the fact that in interpreted communication there is the co-presence of two or more cultural and language systems which inevitably give rise to potential misunderstandings or misinterpretations of the original, intended message issued by the speaker. The point of departure of the study is the understanding that besides being language experts, interpreters also need to acquire intercultural effectiveness in order to successfully practice their profession.The study discusses basic concepts of intercultural communication and examines the relationship between interpreting and intercultural awareness, particularly focusing on the role and specific skills of the interpreter. To this effect, a survey was carried out among professional interpreters in the Republic of Macedonia. The aim of the survey was to test interpreters’ point of view of the way they perceive their role during the interpretative event. The importance of including the teaching of intercultural communication as part of the interpreter training program at the Faculty of Philology “Blaže Koneski” – Skopje, will also be highlighted.
Keywords: conference interpreting; intercultural communication; intercultural communicative competence